2018
DOI: 10.5005/jp-journals-10024-2253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Fluoride Prophylactic Agents on Mechanical Properties of Nickel Titanium Wires using Scanning Electron Microscope

Abstract: Introduction Orthodontic treatment these days is increasing in demand, and therefore, it is relatively imperative for the orthodontist to prescribe the use of fluoride-containing products, such as mouthwashes and gels, to help prevent dental caries and maintain healthy oral health. The aim of the study was to assess and evaluate the effects of fluoride prophylactic agents on mechanical properties of nickel titanium (NiTi) wires during orthodontic treatment using scanning electron microscope (SEM). Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, previous research shows that using fluoride-containing agents with low or high concentrations is insufficient to prevent or treat WSLs [ 9 ]. A high concentration of fluoride could significantly affect NiTi wires by affecting its mechanical properties [ 10 , 11 ] and may increase the risk of chronic fluoride toxicity [ 12 ]. Shielding the enamel surface with orthodontic sealants has been suggested to minimize enamel demineralization next to orthodontic brackets [ 4 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research shows that using fluoride-containing agents with low or high concentrations is insufficient to prevent or treat WSLs [ 9 ]. A high concentration of fluoride could significantly affect NiTi wires by affecting its mechanical properties [ 10 , 11 ] and may increase the risk of chronic fluoride toxicity [ 12 ]. Shielding the enamel surface with orthodontic sealants has been suggested to minimize enamel demineralization next to orthodontic brackets [ 4 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies [24,35,37,39,40,42,43] demonstrated the effect of fluoride gel on the tissue surface of human or bovine teeth, all of which showed increased surface remineralization. Three articles [8,25,34] also demonstrated the effect of fluoride gel on the surface of stainless steel and titanium alloys, with defects observed in all cases. Additionally, one in vivo study [44] was conducted on the surface of stainless steel and metal alloys.…”
Section: Main Study Outcomesmentioning
confidence: 97%
“…After a full-text examination, six articles were rejected due to not meeting the inclusion criteria. Finally, 17 articles qualified for the systematic review [8,12,24,25,[34][35][36][37][38][39][40][41][42][43][44][45][46]. All of the included studies were written in English and were either in vitro or in vivo studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations